Reading, writing, mathematics and the developing brain : ristening to many voices - Breznitz, Zvia (Literacy Studies, Perspectives from Cognitive Neurosciences, Linguistics, Psychology and Education, 2012)
This valuable addition to the literature offers readers a comprehensive overview of recent brain imaging research focused on reading, writing and mathematics-a research arena characterized by rapid advances that follow on the heels of fresh developments and techniques in brain imaging itself. With contributions from many of the lead scientists in this field, a number of whom have been responsible for key breakthroughs, the coverage deals with the commonalities of, as well as the differences between, brain activity related to the three core educational topics. At the same time, the volume addresses vital new information on both brain and behavior indicators of developmental problems, and points out the new directions being pursued using current advances in brain imaging technologies as well as research-based interventions. The book is also a tribute to a new Edmund, J Safra Brain center for the study of learning Disabilities at the University of Haifa-Israel.